Synthesis, Characterization, and Pesticidal Activity of Emamectin Benzoate Nanoformulations against Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Asem Elabasy; Ali Shoaib; Muhammad Waqas; Mingxing Jiang; Zuhua Shi (Molecules, 2019)
Using nanotechnology to develop new formulations of pesticides is considered a possible option in enhancing the efficiency, safety, and photostability of pesticides under various climatic conditions. In the present study, two novel nanoformulations (NFs) were successfully prepared based on nano-delivery systems for emamectin benzoate (EMB) by loading it on cellulose nanocrystals (CNCs) and silicon dioxide nanoparticles (SNPs) as carriers through a freeze-drying method. The synthesized nanoformulations were examined using field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and dynamic light scattering (DLS). The results showed that SNPs and CNCs had a loading efficiency of 43.31% and 15.04% (w/w) for EMB, respectively, and could effectively protect EMB from photolysis under UV radiation. The LC50 values for EMB + SNPs, EMB + CNCs, and EMB commercial formulation against Phenacoccus solenopsis were 0.01, 0.05, and 0.31 μg/mL, respectively, indicating that both NFs were more effective than the EMB commercial formulation. This work seeks to develop new nano-carriers for potential applications of pesticides in plant protection, which will reduce the recommended dose of pesticides and thereby decrease the amount of pesticide residue in food and the environment.